THE EFFECT OF BLENDED LEARNING MODEL ON STUDENTS' LEARNING OUTCOMES ON THE THEME OF “LINGKUNGAN SAHABAT KITA” AT GRADE V SD - Levianti Simandalahi; Patri Janson Silaban; Reflina Sinaga (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2021)
This study aimed to determine the effect of Blended Learning model on students’ learning outcomes on the theme of “Lingkungan Sahabat Kita” at grade V SD Negeri 060937 Kecamatan Medan Johor for the academic year 2020/2021. This study was carried out in April 2021. In this study, the analytical descriptive method was used. The research population was the fifth grade students of SD Negeri 060937, Kecamatan Medan Johor, which contained 2 classes with a total of 40 students. The samples in this study were selected by using simple random sampling and obtained as many as 20 people. The results of this study indicated that students’ learning outcomes after implementing Blended Learning model was in very good category with an average score of 81.4. The results of this study indicated that the results of the correlation test was 0.881, meaning that rcount (0.881) > rtable (0.444). Thus, Ha was accepted. Furthermore, the results of testing the hypothesis found that tcount > ttable which was 7.907 > 1.734, so it could be said that Ha was accepted. This showed that there was Blended Learning model gave a significant positive influence on students’ learning outcomes on the theme of “Lingkungan Sahabat Kami” at grade V SD Negeri 060937, Kecamatan Medan Johor , for the academic year 2020/2021. Thus, Blended Learning model could be used in the learning process on the theme of “Lingkungan Sahabat Kami”.